Noble Metal-Free Nanoporous High-Entropy Alloys as Highly Efficient Electrocatalysts for Oxygen Evolution Reaction - Qiu, Hua-Jun; Fang, Gang; Gao, Jiaojiao; Wen, Yuren; Lv, Juan; Li, Huanglong; Xie, Guoqiang; Liu, Xingjun; Sun, Shuhui (ACS materials letters, 2019)
Developing highly efficient catalysts for oxygen evolution reactions (OER) is a key step for rechargeable metal–oxygen batteries and water splitting. Usually, binary NiFe or ternary NiCoFe nano-alloys are used as the OER catalysts. Herein, combining the precursor alloy design with chemical etching, a simple dealloying route is developed to controllably incorporate five or more nonprecious metals into one nanostructured alloy with a naturally oxidized surface, that is, nanoporous high entropy alloys (np-HEAs) covered with high-entropy (oxy)hydroxides (HEOs). It is found that the alloy composition plays a dominant role in the OER activity enhancement with the np-AlNiCoFeX (X = Mo, Nb, Cr) combination showing the highest activity. Forming quinary HEAs also greatly enhances the electrochemical cycling stabilities compared with the ternary and quaternary counterparts. The result indicates the significance of synergistically incorporating five or more metal elements in one single-phase nanostructure, which provides more structural and chemical degrees of freedom to boost the catalytic performance, overcoming the restriction of normal binary or ternary alloys. Multinary transition metal-based np-HEA is a new class of promising catalyst for various important reactions.